PTU-115 Hepatitis B in Pregnancy: what Happens to the Infants?. (4th June 2013) - Dyson, J; Waller, J; Michael, E; Turley, A; Moses, S; Valappil, M; Hudson, M; Bassendine, M; McPherson, S
Abstract : Introduction: Antenatal screening for Hepatitis B (HBV) has been offered to all pregnant women in the UK since 2000. Immunoprophylaxis of infants is essential to reduce the risk of vertical transmission. It is recommended that HBV vaccination (4 serial doses) be given to all infants born to HBV positive mothers. In addition, Hepatitis B immunoglobulin (HBIG) is recommended for infants of Hepatitis B e antigen (HBeAg) positive mothers. Infants should have post-vaccination testing between 9–18 months. Hepatitis B surface antigen (HBsAg) negative infants with anti-HBs levels > 10iu/ml need no further management. If anti-HBs is < 10iu/ml infants should receive a second vaccination series. Our aim was to evaluate the management of infants born to HBV positive mothers. Methods: All HBV positive pregnant women seen in our hospital between January 2008 and November 2011 were identified from an obstetric database. We examined if the infants received the recommended vaccinations, HBIG and post-vaccination testing. Results: From a total of 99 pregnancies data was available for 76 infants. All 15 infants born to HBeAg positive mothers were given HBIG at birth. 7 mothers had a HBV DNA > 107 IU/ml. 2 were treated with antiviral therapy during pregnancy. 58 (76.3%) infants received a full vaccination course. Only 35 (54.7%) of the 64 infants who should have had their post-vaccination status checked to date have had this completed. 34 (97.1%) had an adequate response to vaccination. One infant (who received 3 vaccinations) is HBsAg positive with a viral load of 5.4 × 103 iu/ml. The mother was HBeAg negative with a viral load of 1.7 × 103 iu/ml. Conclusion: HBIG was administered appropriately to the infants at highest risk of vertical transmission of HBV. However, completion of the 4 dose HBV vaccination in infants was suboptimal postpartum and post- vaccination testing was inadequate. Efforts to improve this are now in place and include: prospective data collection to improve quality of data; development of a central reminder system to advise family doctors 2 weeks before each vaccination dose is due and ensure this is completed; and introduction of dry blood spot testing of the infants to improve the acceptability of testing. Disclosure of Interest: None Declared